Sistem Informasi Customer Service Berbasis WEB pada PT. Telekomunikasi Indonesia, Tbk. (TELKOM) Jember - Ashrifa, Diba; Rahman, Miftahur; Maryam Zakiyyah, Amalina (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
PT Telekomukasi Indonesia, Tbk (Telkom) Jember in customer service work such as contacting customers to remind bills every month for those who have just subscribed to products from PT Telekomukasi Indonesia, Tbk (Telkom) Jember. In this work, of course there is data processing that must be detailed and can be done quickly. However, data processing that is still used at PT Telekomukasi Indonesia, Tbk (Telkom) Jember uses an impractical system such as the use of a Google Sheet which then checks the customer's internet number one by one (copy-paste) into another program to find out the number of bills in arrears, then after it contacts those customers and records things like customer complaints. With current technological developments, customer service is made easy and fast. In this research, web development uses the PHP programming language and the method used is the waterfall model. The result of this research is a system that can process calling data. The system can be used by PT Telekomukasi Indonesia, Tbk (Telkom) Jember service officers. With this system, making reports on the results of calls becomes more effective in the form of information data that is input online through the website so that it can produce reports on the results of calls that are ready to be printed or downloaded by the customer service department.